Prevalence of stress and related factors among healthcare students: a cross – sectional study in Can Tho City, Vietnam - Nguyen-Thi, Thanh-Thao; Le, Huu Minh; Chau, Trinh Lieu; Le, Hieu Trung; Pham, Tin Trung; Tran, Nguyet Tu; Ngo, Quyen Phan Minh; Pham, Nhan Hong; Nguyen, Dat Tan (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Stress is a major public health issue that can impact both physical and mental well-being. It is prevalent in many areas of modern life, including education. Healthcare students are at a high risk of experiencing stress due to the unique demands of their fields of study. Study design and methods. An online survey was conducted on 2,515 undergraduate students pursuing degrees in medicine, preventive medicine, pharmacy, and nursing at Can Tho University of Medicine and Pharmacy in Can Tho City, Vietnam. Results. Using the Perceived Stress Scale-10 (PSS-10), it was found that 35.2% of students reported mild stress, 62.7% had moderate stress, and only 2.1% experienced severe stress. Multivariable logistic regression analysis revealed nine significant factors associated with students’ stress levels (p ≤ 0.05). Particularly, medicine students exhibited a significantly higher level of moderate and severe stress (95% CI = 1.22-2.01), 1.57 times higher than preventive medicine students. Sixth-year students had a stress level 1.58 times higher (95% CI = 1.11-2.26) than first-year students. Students achieving excellent and very good academic performances in the last semester had a stress level 1.60 times higher (95% CI = 1.16-2.22) than students with average and lower academic performance. Students living at home had a stress level 1.73 times higher (95% CI = 1.05-2.84) than students living in their relatives’ houses. Students who rarely or never had a part-time job during academic years had a stress level 1.70 times higher (95% CI = 1.31-2.20) than those who often or sometimes had a part-time job. Students with a family history of smoking addiction had a stress level 1.69 times higher (95% CI = 1.28-2.22) than students without such a family history. Students who rarely or never received concern and sharing from family had a stress level 7.41 times higher (95% CI = 5.07-10.84) than students who often or sometimes received concern and sharing from family. Students who were often or sometimes cursed by family had a stress level 2.04 times higher (95% CI = 1.09-3.81) than students who were rarely or never cursed by family. Students without close friends had a stress level 1.46 times higher (95% CI = 1.11-1.91) than students with close friends. Conclusions. The rates of mild and moderate stress levels were significantly higher than severe stress level among healthcare students. Research has provided scientific findings as the basis for determining risk factors and imposing solutions that aim to reduce the rate of stress in students. Therefore, it helps students overcome difficulties and enhance their physical and mental health.